2021
DOI: 10.1177/15589447211044786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient Perception and Satisfaction of Face-to-Face Versus Telemedicine Encounters in Hand Surgery

Abstract: Background: The coronavirus disease 2019 (COVID-19) surge has enabled the widespread usage of telemedicine (TM) and presents a unique opportunity to determine the hand surgery patients’ perception of care using validated patient satisfaction scores. Methods: Electronic surveys were distributed to patients aged 18 years and older who underwent a video TM encounter with a single surgeon at an academic medical center during the initial COVID-19 surge (March 23 to October 22, 2020). The study-specific questions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some examples include feeling comfortable in receiving care virtually (e.g. due to privacy) (n = 8, 17%) [ 17 25 ], feeling safe against COVID-19 (n = 5, 11%) [ 18 , 21 , 26 29 ], communication with healthcare providers (n = 31, 66%) [17, [ 17 , 20 24 , 30 43 ], the convenience of virtual care and saving time (n = 24, 51%) (e.g. minimizing barriers such as transportation, traffic, cost of gas and parking, and associated anxiety) [ 20 23 , 26 , 28 33 , 35 , 37 39 , 43 55 ], access to care (n = 9, 19%) [ 19 , 22 , 24 , 28 , 35 , 38 , 43 45 , 51 , 56 , 57 ], patient engagement in care (n = 4, 9%) [ 36 , 37 , 44 ], comfort in the technology/telehealth system (n = 17, 36%) [ 27 , 28 , 35 , 51 ], and not experiencing wait time delays in seeing their healthcare providers (n = 8, 17%) [ 22 , 28 , 46 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some examples include feeling comfortable in receiving care virtually (e.g. due to privacy) (n = 8, 17%) [ 17 25 ], feeling safe against COVID-19 (n = 5, 11%) [ 18 , 21 , 26 29 ], communication with healthcare providers (n = 31, 66%) [17, [ 17 , 20 24 , 30 43 ], the convenience of virtual care and saving time (n = 24, 51%) (e.g. minimizing barriers such as transportation, traffic, cost of gas and parking, and associated anxiety) [ 20 23 , 26 , 28 33 , 35 , 37 39 , 43 55 ], access to care (n = 9, 19%) [ 19 , 22 , 24 , 28 , 35 , 38 , 43 45 , 51 , 56 , 57 ], patient engagement in care (n = 4, 9%) [ 36 , 37 , 44 ], comfort in the technology/telehealth system (n = 17, 36%) [ 27 , 28 , 35 , 51 ], and not experiencing wait time delays in seeing their healthcare providers (n = 8, 17%) [ 22 , 28 , 46 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Atia et al [17] described checking up on patients less frequently, whereas most of authors used telemedicine to follow up with their patients [12,14,[22][23][24]. This is a method that proved its accuracy [25] and found satisfaction among patients [10,22,26], whereas surgeons had frequent issues [10,22]. The authors did not use telemedicine, and Toia et al [11] as well as Leti Acciaro et al [27] confirmed it might be an issue in Italy.…”
Section: Discussionmentioning
confidence: 99%